Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3 - Page 489: 54



Work Step by Step

Recall the following rule: $a^{n}+a^{m}=a^{n+m}$ Thus, we obtain: $a^{\frac{1}{3}}\times a^{-\frac{1}{4}}$ =$a^{\frac{1}{3}-\frac{1}{4}}$ =$a^{\frac{1(4)-1(3)}{12}}$ =$a^{\frac{4-3}{12}}$ =$a^{\frac{1}{12}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.